2019
DOI: 10.14710/dijb.2.2.2019.112-121
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dividend payout ratio: evidence from Indonesian manufacturing companies

Abstract: The purpose of this study is to investigate and analyze the relationship between return on assets, growth sales, debt to equity ratio, lagged dividend to dividend payout ratio and size as control variable. Data collected from manufacturing industries in Indonesian Stock Exchange 2011-2017. The method of this study is ordinary least square regression. The results of this study shows that return on assets and lagged dividend have positive impact to dividend payout ratio. Growth sales has insignificance negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
1
5
0
3
Order By: Relevance
“…Profitability has a positive effect on dividend policy (Tedja et al, 2020;Hartono and Matusin, 2020;Herdianta and Ardiati, 2018;Putri and Aggrahini, 2021;Sulhan and Herliana 2018;Kusuma et al, 2018). However, in contrast to the results of research by Abdullah (2021), Arseto and Jufrizen (2018), Puspita (2017), Septiani et al (2020), Darmawan and Triyonowati (2020), Kurniawan and Kristamurti (2021), Lestari and Pangestuti (2022), Lohanauman and Budiarso (2021), Wibowo and Triyonowati (2021), Widyawati and Indriani (2019), Jaara et al (2018) which states that profitability has a negative effect on dividend policy. While the results of research by Deitiana et al (2020); Setevanius and Yap (2017); Widyakto and Triyani (2022); Santosa et al (2020) state that profitability has no effect on dividend policy.…”
Section: Introductionmentioning
confidence: 94%
“…Profitability has a positive effect on dividend policy (Tedja et al, 2020;Hartono and Matusin, 2020;Herdianta and Ardiati, 2018;Putri and Aggrahini, 2021;Sulhan and Herliana 2018;Kusuma et al, 2018). However, in contrast to the results of research by Abdullah (2021), Arseto and Jufrizen (2018), Puspita (2017), Septiani et al (2020), Darmawan and Triyonowati (2020), Kurniawan and Kristamurti (2021), Lestari and Pangestuti (2022), Lohanauman and Budiarso (2021), Wibowo and Triyonowati (2021), Widyawati and Indriani (2019), Jaara et al (2018) which states that profitability has a negative effect on dividend policy. While the results of research by Deitiana et al (2020); Setevanius and Yap (2017); Widyakto and Triyani (2022); Santosa et al (2020) state that profitability has no effect on dividend policy.…”
Section: Introductionmentioning
confidence: 94%
“…Berdasarkan konsep siklus kehidupan perusahaan, fase pertumbuhan cenderung mengharuskan perusahaan untuk mengeluarkan dana yang dimiliki dan kebijakan ekspansi untuk persiapan kedepannya yaitu tahap kematangan atau maturity (Widyawati & Indriani, 2019). Kautsar (2014) juga mempunyai pendapat yang sama dan menambahkan bahwa pengeluaran tersebut akan semakin dibutuhkan apabila perusahaan tersebut berorientasi pada industri yang mempunyai tingkat pertumbuhan tinggi.…”
Section: Pertumbuhan Penjualan Dan Dividend Payoutunclassified
“…Some research confirmed a negative relationship between the DER ratio and dividend policy (Halim & Hastuti, 2019;Marina et al, 2020;Sarumpaet & Suhardi, 2019;Sebastian & Siauwijaya, 2021;Trisnadewi et al, 2019). Another study (Widyawati & Indriani, 2019) shows the opposite results, namely the higher the leverage ratio, the higher the level of dividend payments by the company. Other studies show that the leverage ratio does not affect dividend policy (Affandi et al, 2018;Azhariyah et al, 2021;Firdaus & Purba, 2019;Prasetyo et al, 2021;Purba et al, 2019;Wijaya, 2017).…”
Section: Introductionmentioning
confidence: 96%